THE RELATIONSHIP BETWEEN BANKING LEGAL PROTECTION AND CRIMINAL LIABILITY IN THE CASE OF CUSTOMER FUND EMBEZZLEMENT (STUDY OF DECISION NO.107/PID.B/2022/PN.PIN) - Fakhira, Cut Tsania; Indrahayati, Aloysia; Fadhilah, Meita; Setiady, Tri (fakultas hukum universitas PGRI Semarang, 2026)
Banking institutions function as financial intermediaries that channel funds from surplus units to deficit units, and their existence is highly dependent on the principle of trust.One of the most serious challenges faced by banks is the embezzlementofcustomerfundsby internal actors, sometimes using forged documents. This issue is exemplified in Decision No. 107/Pid.B/2022/PN.Pin, which highlights weaknesses in internal banking supervision, causing significant customer losses and undermining the stability of the national financial system. Normatively, embezzlement is regulated under Articles 372 and 374 of the Indonesian Penal Code (KUHP) and specifically addressed in Article 49 paragraph (1) of Law No. 10 of1998on Banking, which imposes criminal sanctions on bank officials or employees who abuse their authority.